Aesthetics of religion: a connective concept - Grieser, Alexandra; Johnston, Jay (Religion and reason, 2017)
This volume is the first English language presentation of the innovative approaches developed in the aesthetics of religion. The chapters present diverse material and detailed analysis on descriptive, methodological and theoretical concepts that together explore the potential of an aesthetic approach for investigating religion as a sensory and mediated practice. In dialogue with, yet different from, other major movements in the field (material culture, anthropology of the senses, for instance), it is the specific intent of this approach to create a framework for understanding the interplay between sensory, cognitive and socio-cultural aspects of world-construction. The volume demonstrates that aesthetics, as a theory of sensory knowledge, offers an elaborate repertoire of concepts that can help to understand religious traditions. These approaches take into account contemporary developments in scientific theories of perception, neuro-aesthetics and cultural studies, highlighting the socio-cultural and political context informing how humans perceive themselves and the world around them. Developing since the 1990s, the aesthetic approach has responded to debates in the study of religion, in particular striving to overcome biased categories that confined religion either to texts and abstract beliefs, or to an indisputable sui generis mode of experience. This volume documents what has been achieved to date, its significance for the study of religion and for interdisciplinary scholarship.